2009
DOI: 10.1186/1757-1626-2-7462
|View full text |Cite
|
Sign up to set email alerts
|

Curing tinnitus with a Cochlear Implant in a patient with unilateral sudden deafness: a case report

Abstract: Cochlear implantation is a routine procedure for patients with bilateral profound sensorineural hearing loss. Some reports demonstrated a suppression of tinnitus as a side-effect after implantation. We describe the case of a 55-year-old man suffering from severe right-sided tinnitus in consequence of sudden right-sided deafness. Multiple therapeutic efforts including intravenous steroids and tympanoscopy with grafting of the round window remained unsuccessful. One year after onset of symptoms right-sided cochl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 8 publications
(12 reference statements)
3
37
0
6
Order By: Relevance
“…Centres in Europe and America have shown that the artificial input of a CI can be integrated in a normal hearing ear and provide binaural hearing benefits while successfully reducing the burden of tinnitus during active CI use [Van de Heyning et al, 2008;Kleinjung et al, 2009;Vermeire and Van de Heyning, 2009;Buechner et al, 2010;Carlyon, 2010;Masgoret et al, 2010;Arndt et al, 2011;Arts et al, 2012;Firszt et al, 2012;Ramos et al, 2012;Gartrell et al, 2014]. Recently, children with UHL have been treated with CI [Hassepass et al, 2013], and the development of appropriate candidacy criteria will be challenging [Boyd, 2014].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Centres in Europe and America have shown that the artificial input of a CI can be integrated in a normal hearing ear and provide binaural hearing benefits while successfully reducing the burden of tinnitus during active CI use [Van de Heyning et al, 2008;Kleinjung et al, 2009;Vermeire and Van de Heyning, 2009;Buechner et al, 2010;Carlyon, 2010;Masgoret et al, 2010;Arndt et al, 2011;Arts et al, 2012;Firszt et al, 2012;Ramos et al, 2012;Gartrell et al, 2014]. Recently, children with UHL have been treated with CI [Hassepass et al, 2013], and the development of appropriate candidacy criteria will be challenging [Boyd, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent tinnitus can have debilitating psychosocial consequences and causes psychiatric distress in 1-3% of the general population [Dobie, 2003]. Currently, there is no cure for tinnitus [Vio and Holme, 2005], and the majority of tinnitus treatment options are primarily directed towards learning to cope with the symptoms to make the patient's daily life less distressing [Noble, 2008;Cima et al, 2012;Langguth et al, 2013].Tinnitus incidence in conventional cochlear implant (CI) candidates with bilateral hearing loss is high, ranging from 66 to 86%, while 34-93% of patients experience a durable suppression of tinnitus after restoration of hearing with a CI [Miyamoto et al, 1997;Quaranta et al, 2004;Baguley and Atlas, 2007;Tyler et al, 2008;Pan et al, 2009;Bovo et al, 2011].Recent studies have shown that a CI can effectively restore binaural hearing in patients with severe-to-profound, sensorineural, unilateral hearing loss (UHL) and helps these patients to find a relief of their concomitant tinnitus [Van den Heyning et al, 2008;Kleinjung et al, 2009;Buechner et al, 2010;Carlyon et al, 2010;Masgoret Palau et al, 2010;Arndt et al, 2011;Ramos et al, 2012;Firszt et al, 2012;Gartrell et al, 2014]. Incapacitating tinnitus in an ear with single-sided deafness (SSD) can affect speech perception in noise in the contralateral ear, while a CI activating the deaf ear at threshold levels can improve the tinnitus and speech perception in noise [Mertens et al, 2013].…”
mentioning
confidence: 99%
“…Kleinjung et al 16 , in 2009, described the case of a man of 55 years who suffered from tinnitus in the right ear as a result of a SSHL. Several therapeutic efforts including intravenous steroids and graft in the round window showed no positive responses.…”
Section: Discussionmentioning
confidence: 99%
“…Estudios recientes [31][32][33] , han demostrado que al realizar un implante coclear en el lado del acúfeno se restauraría el input auditivo y por tanto, la reorganización del sistema nervioso central. Otra posible explicación sería que el propio beneficio auditivo producido por el implante enmascarara el acúfeno y que por tanto éste no fuera audible por el paciente.…”
Section: Implante Coclear En Sordera Unilateralunclassified